Research and Verification on SDN-Based On-Demand Smart Routing System - Xinping Wang; Qian Wang; Enhui Liu; Yiran Ma; Chengyong Lin; Fan Shi (Dianxin kexue)
SDN is a new network technology. Open programmable SDN concept can be perfectly combined with intelligent network pipeline demand. Research on S-NICE architecture has explored in this field. The on demand custom routing system which is a kernel system in the S-NICE architecture was described from several aspects, such as key technologies and system design, deployment and verification, as well as scenarios.